HCN channels in the mammalian cochlea: Expression pattern, subcellular location, and age‐dependent changes. Issue 2 (12th November 2020) - Luque, Maria; Schrott‐Fischer, Anneliese; Dudas, Jozsef; Pechriggl, Elisabeth; Brenner, Erich; Rask‐Andersen, Helge; Liu, Wei; Glueckert, Rudolf
Abstract: Neuronal diversity in the cochlea is largely determined by ion channels. Among voltage‐gated channels, hyperpolarization‐activated cyclic nucleotide‐gated (HCN) channels open with hyperpolarization and depolarize the cell until the resting membrane potential. The functions for hearing are not well elucidated and knowledge about localization is controversial. We created a detailed map of subcellular location and co‐expression of all four HCN subunits across different mammalian species including CBA/J, C57Bl/6N, Ly5.1 mice, guinea pigs, cats, and human subjects. We correlated age‐related hearing deterioration in CBA/J and C57Bl/6N with expression levels of HCN1, −2, and −4 in individual auditory neurons from the same cohort. Spatiotemporal expression during murine postnatal development exposed HCN2 and HCN4 involvement in a critical phase of hair cell innervation. The huge diversity of subunit composition, but lack of relevant heteromeric pairing along the perisomatic membrane and axon initial segments, highlighted an active role for auditory neurons. Neuron clusters were found to be the hot spots of HCN1, −2, and −4 immunostaining. HCN channels were also located in afferent and efferent fibers of the sensory epithelium. Age‐related changes on HCN subtype expression were not uniform among mice and could not be directly correlated with audiometric data. The oldest mice groups revealed HCN channel up‐ or downregulation, depending on the mouse strain. The unexpected involvement of HCN channels in outer hair cell function where HCN3 overlaps prestin location emphasized the importance for auditory function. A better understanding may open up new possibilities to tune neuronal responses evoked through electrical stimulation by cochlear implants. Abstract : All HCN channel subtypes were located at subcellular level in human and compared with other mammals such as guinea pig, cat, and three mouse strains. Changes in HCN expression levels were quantified in aging mice and murine postnatal development. The widespread expression and distinct localization emphasized the importance of HCN channels for sound coding and electrical stimulation with cochlear implants